Physical Exercise as a Supportive Intervention in Attention-Deficit / Hyperactivity Disorder - Kuliś, Gabriela; Dryl-Jarmoc, Ewa; Ślinko, Izabela; Panas, Zuzanna; Zimowski , Mateusz; Dziemiańczuk, Jakub; Czajkowski, Mateusz; Krawczuk, Kacper; Kadysz , Piotr; Kolanek, Agata (Quality in Sport, 2026)
Background. Attention-deficit/hyperactivity disorder (ADHD) is one of the most common neurodevelopmental disorders worldwide and remains an important public health concern. The disorder is characterized by persistent inattention, hyperactivity, and impulsivity that impair functioning across multiple domains. Purpose: This narrative review aimed to synthesize current evidence on the effects of physical activity and structured exercise interventions on cognitive performance, behavioral symptoms, and neurobiological mechanisms in individuals with ADHD. Materials and methods: Peer-reviewed studies published between 2010 and 2025 were identified through PubMed, Scopus, Web of Science, and ScienceDirect. Studies evaluating exercise interventions in people with ADHD and reporting cognitive, behavioral, or neuropsychological outcomes were included. Results: Available evidence suggests that physical exercise may reduce ADHD symptom severity and improve executive functions, especially working memory, inhibitory control, and cognitive flexibility. These effects are likely mediated by neurobiological adaptations involving catecholamines, neurotrophic factors, and enhanced neural efficiency. Conclusions. Physical exercise appears to be a promising adjunctive intervention in ADHD management. Although it should not replace pharmacotherapy when indicated, regular physical activity may strengthen therapeutic outcomes and support cognitive, behavioral, and emotional functioning.